Formulation of food emulsions using natural emulsifiers: Utilization of quillaja saponin and soy lecithin to fabricate liquid coffee whiteners. (September 2017) - Chung, Cheryl; Sher, Alexander; Rousset, Philippe; Decker, Eric Andrew; McClements, David Julian
Abstract: Rising consumer demand for food products made with natural and plant-based ingredients has led to a search for natural alternatives to synthetic food ingredients. The present study compared the ability of two natural small molecule surfactants – quillaja saponin (0.5–2.5%) and soy lecithin (1–5%) – to stabilize 10% oil-in-water emulsions. Emulsion lightness decreased with increasing emulsifier concentration in both systems, which was attributed to the inherent color of the emulsifiers (increased absorption) and the decrease in droplet size (decreased scattering). The mean droplet diameter decreased with increasing emulsifier concentration (0.5–0.15 μm for quillaja saponin and 0.8 to 0.14 μm for soy lecithin) due to their ability to cover more surface area. Both emulsifiers led to the formation of oil droplets with a high negative charge (ζ = −45 to −70 mV), thereby generating a strong electrostatic repulsion that helped protect them against aggregation. The emulsions remained physically stable when added to an acidic hot coffee solution (85 °C), with no visible phase separation or increase in particle size. This study provides insight into the potential of two natural emulsifiers to form stable emulsions suitable for application in coffee creamers. Highlights: The impact of two natural emulsifiers on the formation and properties of coffee creamers was compared. Model creamers were prepared using quillaja saponin and soy lecithin as emulsifiers. Saponin- and lecithin-stabilized creamers had comparable performance as commercial creamers. The creamers were stable to aggregation and separation when added to acidic hot coffee.